SCIENTIFIC-METHODICAL BASIS OF IMPROVING THE ORGANIZATIONAL-ECONOMIC MECHANISM OF MANAGEMENT OF INNOVATIVE ACTIVITY IN INDUSTRIAL ENTERPRISES - Bakhodirov, Shokhruh Bakhodir o‘g‘li (THE INNOVATION ECONOMY, 2026)
This article examines the formation of an improved organizational and economic mechanism for managing innovation activity at industrial enterprises. The purpose of the study is to develop an effective organizational and economic mechanism for innovation management in industrial enterprises. The research is based on systemic, process-based, and situational approaches, as well as comparative analysis, scientific generalization, structural grouping, and logical analysis. As a result, an improved mechanism for managing innovation activity was developed, consisting of target, organizational, economic, information-analytical, and monitoring blocks. The study substantiates that the implementation of this mechanism improves the quality of innovation-related managerial decisions, increases resource efficiency, enhances managerial adaptability, and strengthens the competitiveness of industrial enterprises